Effectiveness of an educational pamphlet for mothers on cooperation of 3-7 years old children in the first dental visit - Motlagh Mehdi Ghandehari; Pourhashemi Seyyed Jalal; Ghadimi Sara; Baghae Farideh (Tehran University of Medical Sciences, 2015)
Background and Aims: Dental environment is a stressful place for children. In many cases, parents transmit their anxiety to their children in the first dental visit. Mothers as the closest person to the children may have important influence on their children's behavior in dentistry. The purpose of this study was to evaluate the effectiveness of an educational pamphlet for mothers on children's behavior in the first dental visit.   Materials and Methods: This study was conducted on 238 mothers who had 3-7 years old children undergoing dental treatment for the first time. The participants were divided into interventional and control group randomly. Behavior of children was assessed by questionnaire according to 4 point scale of Frankle. The questionnaire contained 5 parts: separation of child from the mother, entering the dental room, opening the mouth, communicating with dentist, getting the prize. Data were analyzed using Chi-square test.   Results: The educational pamphlet was effective on the separation of child from the mother, the cooperation of children in interventional group was better than the control group (P=0.006). In interventional group 96.2% of and in the control group 90.8% of children had good and very good behavior but the difference was not significant (P=0.11).   Conclusion: Although the educational pamphlet was effective on the separation of child from mother. No significant difference in behavior of 3-7 year-old children between interventional and control group was found.